A decade of security research in ubiquitous computing: results of a systematic literature review. Issue 2 (6th June 2016) - Kusen, Ema; Strembeck, Mark
Abstract : Purpose: Ever since Mark Weiser coined the term "ubiquitous computing" (ubicomp) in 1988, there has been a general interest in proposing various solutions that would support his vision. However, attacks targeting devices and services of a ubicomp environment have demonstrated not only different privacy issues, but also a risk of endangering user's life (e.g. by modifying medical sensor readings). Thus, the aim of this paper is to provide a comprehensive overview of security challenges of ubicomp environments and the corresponding countermeasures proposed over the past decade. Design/methodology/approach: The results of this paper are based on a literature review method originally used in evidence-based medicine called systematic literature review (SLR), which identifies, filters, classifies and summarizes the findings. Findings: Starting from the bibliometric results that clearly show an increasing interest in the topic of ubicomp security worldwide, the findings reveal specific types of attacks and vulnerabilities that have motivated the research over the past decade. This review describes most commonly proposed countermeasures – context-aware access control and authentication mechanisms, cryptographic protocols that account for device's resource constraints, privacy-preserving mechanisms, and trust mechanisms for wireless ad hoc and sensor networks. Originality/value: To the best of our knowledge, this is the first SLR on security challenges in ubicomp. The findings should serve as a reference to an extensive list of scientific contributions, as well as a guiding point for the researchers' novel to the security research in ubicomp.